Computational statistics handbook with MATLAB - Martinez Wendy L; Martinez Angel R (Boca Raton Chapman & Hall, 2002)
Approaching computational statistics through its theoretical aspects can be daunting. Often intimidated or distracted by the theory, researchers and students can lose sight of the actual goals and applications of the subject. What they need are its key c
Keywords: Computational statistics; MATLAB; Statistical computing